2010
DOI: 10.1111/j.1443-1661.2010.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Healing of Solitary Rectal Ulcers With Multiple Sessions of Argon Plasma Coagulation

Abstract: APC controls bleeding in patients with SRUS and it also improves the healing of these ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
2
15
0
1
Order By: Relevance
“…The coagulated surface undergoes the processes of superficial coagulation necrosis as a result of mucous membrane blanching, water evaporation and tissue shrinking. This involves only the superficial layer [6, 9, 10]. The APC was effective in stopping the bleeding in our case and other authors’ cases.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The coagulated surface undergoes the processes of superficial coagulation necrosis as a result of mucous membrane blanching, water evaporation and tissue shrinking. This involves only the superficial layer [6, 9, 10]. The APC was effective in stopping the bleeding in our case and other authors’ cases.…”
Section: Discussionsupporting
confidence: 63%
“…The APC was effective in stopping the bleeding in our case and other authors’ cases. It seems to be effective also in healing solitary rectal ulcer syndrome [6, 10]. …”
Section: Discussionmentioning
confidence: 99%
“…The selection and success of therapy varies from patient to patient. Recently, the argon plasma coagulation technique has been reported to be effective in SRUS therapy (11). Patients should also be discouraged from using the digital stimulation technique to ease defecation.…”
Section: N Discussionmentioning
confidence: 99%
“…Argon plasma coagulation has been used to treat haemorrhage from SRUS. Somani et al [19] showed that combined dietary therapy, biofeedback, and argon plasma coagulation allowed bleeding control in 100%, complete healing of ulcers in 75%, and a reduction in ulcer size in the remaining 25% of their patients. Among the 24 patients, paediatric patients were included.…”
Section: Discussionmentioning
confidence: 99%